Experimental mode shape determination of a cantilevered hydrofoil under different flow conditions. (December 2016) - De La Torre, O; Escaler, X; Egusquiza, E; Farhat, M
The first three mode shapes of a cantilevered NACA0009 hydrofoil were experimentally investigated in air and under different flow conditions in a cavitation tunnel. First and second bending modes and first torsion mode were determined in resonance conditions with the hydrofoil vibrating in air, in still water, in flowing water, or with leading edge sheet cavitation. The hydrofoil was excited with embedded piezoelectric ceramic patches, and the response was measured along the surface at selected positions by means of a laser Doppler vibrometer. The modes of vibration obtained from a cross correlation analysis of the signals were compared for the different conditions, and the most significant differences were identified. In particular, it was found that the mode shape deformation and the location of the nodal lines are dependent on the fluid conditions.